2018
DOI: 10.2147/jpr.s153660
|View full text |Cite
|
Sign up to set email alerts
|

The ultrasound-guided retrolaminar block: volume-dependent injectate distribution

Abstract: PurposeThe ultrasound-guided retrolaminar block is one of the newer and simpler alternatives to the traditional, often technically challenging, paravertebral (PV) block. Its feasibility, safety, and efficacy have already been clinically demonstrated in patients with multiple rib fractures using higher volumes of local anesthetic, when compared with the traditional approach. The primary aim of this observational anatomical study was to assess the spread of local anesthetic from the retrolaminar injection point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 27 publications
(33 reference statements)
1
36
1
1
Order By: Relevance
“…Our results suggest that a multi-level injection procedure may not be an advantageous technique for RLB. A recent anatomical study on pigs demonstrated that the local anesthetic distribution from the retrolaminar space to the paravertebral space was volume dependent (Damjanovska et al 2018). We cannot directly apply their results to humans due to anatomical differences between the species.…”
Section: Discussionmentioning
confidence: 92%
“…Our results suggest that a multi-level injection procedure may not be an advantageous technique for RLB. A recent anatomical study on pigs demonstrated that the local anesthetic distribution from the retrolaminar space to the paravertebral space was volume dependent (Damjanovska et al 2018). We cannot directly apply their results to humans due to anatomical differences between the species.…”
Section: Discussionmentioning
confidence: 92%
“…Pressure exerted during injection of a large volume of dye in the ESP has also been postulated to favor its spread into the PVS 5 21. However, the pressure exerted during injection should theoretically be ‘consumed’ in the path of least resistance favoring fluid toward the ESP,22 without forcing its passage through the anatomical barrier existing between the epaxial and hypaxial muscle compartments,11 regardless of the volume injected 21. In this study, neither the pressure exerted nor the injection of a large volume (equivalent to 40 mL in a 70 kg human) produced real-time US-visible changes in the PVS compatible with anterior spread of dye.…”
Section: Discussionmentioning
confidence: 99%
“…Another cadaveric study, using magnetic resonance imaging and anatomical dissection, demonstrated that the RLB with 20 mL of injectate produced spread into the epidural and neural foramen spaces [ 24 ]. However, the pattern of injectate spread was variable [ 25 ], and the extent of paravertebral distribution could be volume-dependent [ 26 ]. Furthermore, most of these human anatomical studies had in common that the RLB was consistently associated with a large distribution of injectate posterior to the back muscle and with limited spread to the paravertebral block [ 24 , 25 , 27 ].…”
Section: Discussionmentioning
confidence: 99%